Assessment of obstacles to sports participation among female students at Kalar University, College of Basic Education - Asad, Prof. Dr. Majid Khoda Yakhsh; Aref, L.D. Mani Ahmed; Ahmed, Asst.prof.Dr. Haider Bawa Khan (Sulaimani Journal for Humanities, 2026)
The research aimed to identify the obstacles to practicing sports among female students at Kalar University, to evaluate the obstacles to practicing sports among female students at Kalar University. The researchers assumed that, firstly: there are many obstacles in the educational, social, economic, training, desire and interest fields that hinder female students at Kalar University from practicing sports. Secondly: educational and social obstacles are among the most significant obstacles that limit female students' practice of sports at Kalar University. The researchers used the descriptive survey method as it was suitable for the nature of the research. The research population was defined as female students at Kalar University, numbering (2620) students representing (7) colleges and (2) departments. The research sample was then selected by chance from the selected colleges, representing (20%) of the total number of female students in each college, and the sample size was (524) students. As for the means of data collection, the researchers used a standardized questionnaire after modifying it and presenting it to experts to ensure its validity, reliability, and objectivity. The researchers distributed it to the research sample, then entered the data and processed it statistically using the SPSSK statistical package, version 25, and the Excel program. Researchers reached several conclusions, including that the various obstacles limiting female students' participation in sports at Kalar University are primarily educational and social. The most significant obstacles include societal disapproval of female students' participation in sports, a lack of social awareness negatively impacting their engagement, and family opposition to their involvement in sports activities. The most prominent economic obstacles were the scarcity of necessary equipment for students to practice sports effectively, the limited number of dedicated sports facilities for female students on campus, and weak encouragement and incentives from both parents and university officials, all of which contributed to low student interest in sports. The most significant obstacles related to desire and interest were: "I have no desire to participate in sports," "I am not interested in sports competitions," and "I prefer to follow other programs." The researchers made several recommendations, including: 1- The need for proper scientific planning for female students to practice sports. 2- Emphasizing the dissemination of sports culture among female students by highlighting the importance of sports for female students. 3- Emphasizing the provision of necessary equipment for female students to practice sports at the university.
Keywords: Assessment; obstacles; sports participation; female university students